Aduceţi fiecare expresie la o formă mai simplă,apoi aflaţi valoarea:a)4x+26x-7x+2x, pentru x=14;
b)41a-8a-13a+13a, pentru a=101;
c)19x+24x-16+x, pentru x=11;
d)22-5x-x-4, pentru x=0;
e)3a*2b, pentru a=5 şi b=10;
f)12x*4y*3, pentru x=2 şi y=3

1

Răspunsuri

Cel mai inteligent răspuns!
2014-10-21T14:43:36+03:00
A) 14(4+26-7+2)
14*25=350
b) 101(41-8-13+13)
101*33=3333
c)11(19+24)-16+11
11*43-16+11=473-16+11=468
d)22-0(5-1)-4=22-0-4=22-4=18
e)(3*2)(a*b)=(3*2)(5*10)=6*50=300
f)(12*4)(x*y)*3=(12*4)(2*3)*3=48*6*3=864
11 3 11